(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This paper examines the pedagogical significance of integrating digital tools into graphic design education. It evaluates the didactic and methodological potential of CorelDRAW and Photoshop in fostering creative thinking, visual literacy, and professional competencies. The study proposes strategies for effective instructional design within digital learning environments.